Developing Construct 2 Android-Based Education Math Game to Improve the ICT Literacy on Number Patterns Subject - Fatahillah, Arif; Alfiyantiningsih, Nur; Dafik, Dafik (Universitas Islam Raden Intan Lampung, INDONESIA, 2021)
This research aimed to describe the development process and results of the Construct 2 Android-based education math game on number pattern subjects to increase student's ICT literacy. This research employed the Research and Development method with a 4-D development model. The development model consisted of 4 stages: the Define stage, the Design stage, the Development stage, and the dissemination stage. Also, the researchers developed the Android-based application based on ICT literacy indicators. The application must be valid, practical, and effective. The results showed a correlation coefficient value of 0.87 and included in the valid category with very high interpretation. The level of practicality of the developed product was 83.96% based on a users' responses questionnaire. The effectiveness was determined based on the percentage of students' learning outcomes which was 83.33%. The increase in students' ICT literacy was determined based on the ICT literacy questionnaire and learning outcome tests' average N-Gain score. The average N-Gain value obtained was 0.75, with an average value for the ICT literacy questionnaire of 0.89 and the average value for the learning outcome test of 0.61. Based on these three criteria, it can be concluded that the Construct 2 android-based educational math game on the number pattern material can improve students' ICT literacy.